CHAIR - Hadjimitsis, Diofantos G. (My University, 2026)
On 5th of October 2023 the Cyprus University of Technology, the Department of Electronic Communications of the Deputy Ministry of Research, Innovation and Digital Policy and the ERATOSTHENES Centre of Excellence organized an event on "Gender, Science and Earth Observation: Strategies to support gender responsive leadership’’. The event hosted Prof. Maria Rentetzi, Head of the Chair of Science, Technology and Gender Studies, Friedrich-Alexander University, Erlangen-Nürnberg and MsBarbara Ryan, Executive Director of the World Geospatial Industry Council (WGIC) and Member of the Board of Directors of the ERATOSTHENES Centre of Excellence for keynote speeches. Prof. Rentetzigave a historical overview of the role of gender in Science and Technology and MsBarbara Ryan addressed the gender dimension in the field of Earth Observation. The speeches were followed by a panel discussion on "Strategies to support gender responsive leadership at ERATOSTHENES Centre of Excellence". Watch the event via YouTube: https://youtu.be/CdH6df7J4h0